Distribution Pattern of Rice (Oryza sativa L.) Roots Under Different Timing and Duration of Water Deficit - Alfu Laila; Sriyanto Waluyo (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2016)
In Indonesia, Rice (Oryza sativa L.) is the most important food crop. In rice cultivated areas, there is a major problem of water deficit. The objective of this study was to investigate the effects of different timings and durations of drought stress on root distribution patterns of rice. The experiment was conducted in Greenhouse at Faculty of Agriculture, Gadjah Mada University, Yogyakarta. A rice genotype IR64 was used in the experiment. Drought stress was imposed for 0 (well-watered treatment), 7, 14 and 21 days by withholding watering at vegetative phase, reproductive phase and generative phase. The result showed that the root’s response was depends on the timing plant growth stages. Under drought stress condition during vegetative growth stage resulted inhibition of root growth and reduced root dry weight. In contrast, under drought stress during reproductive stages, roots grew vigorously below 48 cm of the soil layer. Drought stress during generative stage reduced root dry weight each layer. Drought stress during 7 and 14 days at different beginning times could change the roots grew deeper than under well-watered condition. Dry weight of root in each lower soil layers was higher than under well-watered conditions. In contrast, drought stress during 21 days had reduced root dry weight each soil layer.